KOORDINASI PENGADILAN NEGERI DAN KEPOLISIAN DALAM PELAKSANAAN EKSEKUSI PUTUSAN HAKIM DALAM PERKARA TANAH ADAT - Robert K (Ensiklopedia Education Review, 2023)
Execution of a decision that has permanent legal force (inkracht van gewijsde) is the final step in resolving a dispute in court. To get their rights, the winning party hopes that execution will be carried out and the losing party is required to comply by fulfilling its obligations as stated in the verdict. However, in reality, in the implementation of the decision (execution), the losing party often does not want to carry out the decision voluntarily, the implementation of the judge's decision is carried out by force by the executor with the help of public power such as the Police.Keywords: Execution, Decision, Indigenous Land